Protection Against Helicobacter pylori Infection in BALB/c Mouse Model by Oral Administration of Multivalent Epitope-Based Vaccine of Cholera Toxin B Subunit-HUUC - Pan, Xing; Ke, Hong; Niu, Xiaojuan; Li, Shan; Lv, Jun; Pan, Longrui (Frontiers in Immunology, 2018)
Vaccination is an increasingly important alternative approach to control H. pylori infection, since H. pylori resistance to previously efficacious antibiotic regimens is increased, and H. pylori eradication treatment for upper gastrointestinal diseases is becoming less successful. Fortunately, an efficient oral monovalent H. pylori vaccine has been developed. However, compared with monovalent vaccines, multivalent vaccines have the potential to induce more effective and comprehensive protection against H. pylori infection. In this study, we designed and produced a multivalent epitope-based vaccine CTB-HUUC with the intramucosal adjuvant CTB and tandem copies of B-cell epitopes (HpaA132-141, UreA183-203, and UreB321-339) and T-cell epitopes (HpaA88-100, UreA27-53, UreB229-251, UreB317-329, UreB373-385, UreB438-452, UreB546-561, CagA149-164, and CagA196-217) from HpaA, UreA, UreB, and CagA. Serum IgG, stomach and intestine mucosal sIgA from mice after CTB-HUUC vaccination neutralized H. pylori urease activity in vitro. CTB-HUUC vaccination promoted H. pylori specific lymphocyte responses and a mixed CD4+ T cell immune response as indicated by IFN-γ, IL-4 and IL-17 production in mice. Both oral prophylactic and therapeutic CTB-HUUC vaccinations reduced gastric urease activity and H. pylori infection, and protected stomachs in mice. Taken together, CTB-HUUC is a promising potent and safe multivalent vaccine in controlling H. pylori infection in BALB/c mice model.